2018
DOI: 10.11118/actaun201866041065
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens in Processed Ram Semen and Approaches for Their Elimination

Abstract: A variety of pathogenic contaminants might be isolated from semen, processed for artificial insemination (AI) programs: prions, viruses, bacteria, yeasts or protozoa. This review will discuss the broad scale of pathogens detected in processed ram semen. Reviewed findings will be confronted with the latest knowledge related to semen contamination in other livestock species. An accent will be placed on current experience and future aspects of approaches for elimination of pathogens from processed semen (especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hence, quality of frozen-thawed semen is an important factor that predicts bull fertility and the sustainability of AI as well as investment of bulls with high genetic merits [7]. However, quality of semen can be altered, among others, by the process of cryopreservation [8][9][10][11][12][13], types of extender used [14], and bacterial contamination [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, quality of frozen-thawed semen is an important factor that predicts bull fertility and the sustainability of AI as well as investment of bulls with high genetic merits [7]. However, quality of semen can be altered, among others, by the process of cryopreservation [8][9][10][11][12][13], types of extender used [14], and bacterial contamination [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally infected sheep did not exhibit any clinical signs of infection (fever, abortion, stillbirth) when tested. T. gondii can also be sexually transmitted through semen (de Moraes et al 2010;Lopes et al 2013), with infected rams becoming infertile (Savvulidi et al 2018).…”
Section: Toxoplasmosis In Wild Animalsmentioning
confidence: 99%
“…Infections and subsequent inflammation in the male genital tract may adversely influence the sperm cell function and the entire spermatogenetic activity (Fraczek & Kurpisz, 2015; Lu et al., 2013), and may cause qualitative and quantitative sperm transformations. Many microbial species may survive in the semen even after cryopreservation (Savvulidi et al., 2018). Retrospective studies have shown that merely presence of bacteria in semen samples may compromise the sperm fertilising ability.…”
Section: Introductionmentioning
confidence: 99%